MODELOS MENTALES TEMPO-ESPACIALES TEMPO-SPATIAL MENTAL MODELS - Alfaro Vargas, Roy (2012)
This article analyzes, within the Costa Rican literary development, the relation between the cronotope of city and the urban cronotope, as a means to set up the concept of tempo-spatial mental models, by introducing concepts from several disciplines: philosophy, sociology, physics, mathematics, etc. At the same time, it exceeds the literary dominion, as part of the concept of praxis. Finally, the “tempo-spatial mental models” are assumed in its political dimension as a means to criticize the establishment and build a socialist society.